Strategic business alliances : an examination of the core dimensions - Glaister, Keith W.; Husan, Rumy.; Buckley, Peter J., 1949- (Cheltenham : Edward Elgar, 2004)
This text examines key issues in the analysis and management of international joint ventures - motives for formation, partner selection criteria, joint venture management, control and performance, which have been identified as the core dimensions of joint venture activity.
Includes bibliographical references and index.
oif 23/03/15
Loan
Keywords: Strategic alliances (Business).; Joint ventures; International business enterprises; Investments, Foreign -- Management